Philosophical Overview of the Relationship between Budget Users and the State General Treasurer in the Management of Financial State (Indonesia Experience) - Achmat Subekan; Azwar Iskandar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Legislation on state financial management is a legal form of state financial management that has a rationale. Understanding the philosophical basis of the rationale will provide strengthening of understanding of the relevant laws and regulations and authority and responsibilities to the Budget User and the State General Treasurer. This study aims to find out the rationale used in state financial management, especially related to the authority and division of responsibility between the Budget User and the State General Treasurer in the state financial management.  This research uses descriptive qualitative method with library research and cotent analysis technique with normative juridical approach . The results found that the Budget User and the State General Treasurer had an equal standing under the President. Both are packaged in check and balance relationships to protect the country's finances from arbitrary actions by certain parties. Philosophically, the Budget User is a party that "has a budget" so that it gets authority in planning the budget, implementing the budget, testing the bill, ordering payments, and accounting for the implementation of the budget. Budget Users become active parties in the implementation of the budget. Meanwhile, the State General Treasurer becomes a passive party, i.e. only carrying out payment duties in accordance with the pay orders issued by the Budget User. The Budget User becomes the party formally and materially responsible for the pay order issued, while the State General Treasurer is formally responsible for the payment.